From Regional to Intercultural Education in Polish Kindergartens - Barbara Surma (Ignatianum University Press, 2019)
Multiculturalism as a social phenomenon requires from education to solve some issues concerning cultural identity shaping, education into dialogue which supports subjectivity, tolerance, acceptance, dignity and recognition. Culture is to help a child to understand himself, to create his own identity, as well as to be able to participate in the creation of modern civilization and to become orientated in the surrounding reality. Fast technological changes as well as easy access to information make it possible to penetrate and to get knowledge about diterent cultures. The goal of education is to shape in a child the abilities to interpret reality, to see cultural similarities and diterences and to be able to make good evaluation. In order to understand multiculturalism and to educate into peaceful coexistence of diterent cultures, one vrst needs to help a child to get to know and to appreciate his own culture. It can be done by introducing a child to regional education. Striking roots into one's own culture, without tendency to be closed in only one culture, can be of help in understanding other people and in overcoming the stereotypes concerning the fear of accepting cultural diterences. The next step towards multicultural dialogue is intercultural education. Drawing attention to the need of studying foreign languages by kindergarten children allows initiating intercultural dialogue. Regional and intercultural education in kindergarten open children to the world and satisfy their cognitive interests.